From Tradition to Future: Sundanese Indigenous Laws as the Vanguard of Environmental Conservation and Disaster Mitigation - Dimas Febriansyah Krisna Dwiputra; Enok Maryani; Fahmi Nugraha Heryanto (The Journal of Indonesia Sustainable Development Planning, 2024)
Environmental conservation and disaster mitigation still emphasize science and technology, while the potential of the socio-cultural wealth within communities remains underutilized. This shows a substantial gap, as active community involvement, rooted in socio-cultural wealth, is essential for effective environmental conservation and disaster mitigation. To address the existing gap, this research aims to identify, analyze, and interpret the values of Sundanese Indigenous laws (Pikukuh) that can be utilized and relevant for these efforts. This study used a qualitative method with a case study design in Kampung Naga, Baduy, Kuta, and Cikondang. The results showed that Pikukuh embodied important values for environmental conservation efforts. These rules played a significant role in conserving forests, improving vegetation conditions, enhancing rainwater absorption, ensuring soil stability, preventing erosion, and maintaining the groundwater cycle. These principles are crucial for mitigating natural disasters like landslides, floods, droughts, and climate change. Pikukuh principles need to be incorporated more broadly and actively applied in policies and strategic initiatives to advance sustainable development, as this goes beyond romanticizing traditions and is essential for securing a sustainable future life